HIPONATREMIA PADA SEORANG PENDERITA DENGAN KECURIGAAN INSUFISIENSI ADRENAL - Sri Yenny, Luh Gede; Gotera, Wira (journal of internal medicine, 2007)
Hyponatremia is defined as a decrease in the serum sodium concentration to a level below 135 mmol perliter. Hyponatremia can be associated with low, normal, or high tonicity. One cause of hyponatremia is adrenalinsufficiency. Serum sodium concentration is regulated by stimulation of thirst, secretion of ADH, feedbackmechanisms of the renin-angiotensin-aldosterone system, and variations in renal handling of filtered sodium.Increases in serum osmolarity above the normal range (280-300 mOsm/kg) stimulate hypothalamicosmoreceptors, which, in turn, cause an increase in thirst and in circulating levels of ADH. ADH increases freewater reabsorption from the urine, yielding urine of low volume and relatively high osmolarity and, as a result,returning serum osmolarity to normal. Aldosterone, synthesized by the adrenal cortex, is regulated primarily byserum potassium but also is released in response to hypovolemia through the renin-angiotensin-aldosterone axis.Aldosterone causes absorption of sodium at the distal renal tubule.In this report, patient is male, 64 years old, with probable adrenal insufficiency. Patient have very lowrespond to sodium teraphy. The sodium level increased and have good respond after corticosteroid teraphy.Patient have low level of cortisol serum (18,60 ?/dl) in critically ill condition.The possibility of adrenal insufficiency is of crucial importance in critically ill patients. If the diagnosisis missed, the patient will probably die. In such patients, a blood sample for the measurement of plasma cortisoland corticotropin should be obtained, a short corticotropin test (see below) should be performed, and immediatehigh-dose cortisol therapy should be considered or instituted. A plasma cortisol value in the normal range doesnot rule out adrenal insufficiency in an acutely ill patient. On the basis of a recent study of plasma cortisolconcentrations in patients with sepsis or trauma, a plasma cortisol value of more than 25 ?g per deciliter in apatient requiring intensive care probably rules out adrenal insufficiency, but a safe cutoff value is unknown.